Effect of selectively knocking down key metabolic genes in Müller glia on photoreceptor health. Issue 8 (9th April 2021) - Shen, Weiyong; Lee, So‐Ra; Mathai, Ashish Easow; Zhang, Rui; Du, Jianhai; Yam, Michelle X.; Pye, Victoria; Barnett, Nigel L.; Rayner, Cassie L.; Zhu, Ling; Hurley, James B.; Seth, Pankaj; et al.
Abstract: The importance of Müller glia for retinal homeostasis suggests that they may have vulnerabilities that lead to retinal disease. Here, we studied the effect of selectively knocking down key metabolic genes in Müller glia on photoreceptor health. Immunostaining indicated that murine Müller glia expressed insulin receptor (IR), hexokinase 2 (HK2) and phosphoglycerate dehydrogenase (PHGDH) but very little pyruvate dehydrogenase E1 alpha 1 (PDH‐E1α) and lactate dehydrogenase A (LDH‐A). We crossed Müller glial cell‐CreER (MC‐CreER) mice with transgenic mice carrying a floxed IR, HK2, PDH‐E1α, LDH‐A, or PHGDH gene to study the effect of selectively knocking down key metabolic genes in Müller glia cells on retinal health. Selectively knocking down IR, HK2, or PHGDH led to photoreceptor degeneration and reduced electroretinographic responses. Supplementing exogenous l ‐serine prevented photoreceptor degeneration and improved retinal function in MC‐PHGDH knockdown mice. We unexpectedly found that the levels of retinal serine and glycine were not reduced but, on the contrary, highly increased in MC‐PHGDH knockdown mice. Moreover, dietary serine supplementation, while rescuing the retinal phenotypes caused by genetic deletion of PHGDH in Müller glial cells, restored retinal serine and glycine homeostasis probably through regulation of serine transport. No retinal abnormalities were observed in MC‐CreER mice crossed with PDH‐E1α‐ or LDH‐A‐floxed mice despite Cre expression. Our findings suggest that Müller glia do not complete glycolysis but use glucose to produce serine to support photoreceptors. Supplementation with exogenous serine is effective in preventing photoreceptor degeneration caused by PHGDH deficiency in Müller glia. MAIN POINTS: Effect of selectively knocking down key metabolic genes in Müller glia on photoreceptor health Müller glia use glucose to produce serine to support photoreceptors. The lactate shuttle hypothesis may not reflect the metabolic relationship between Müller glia and photoreceptors in the retina.